CASE-BASED REASONING UNTUK MENJAGA MUTU PELAYANAN PURNA JUAL OTOMOTIVE - Choiri, Mochammad; Santoso, Purnomo Budi (JEMIS (Journal of Engineering & Management in Industrial System), 2015)
Abstract Customer satisfaction was the main business factor. After sales service was one of the most important to ensure customer satisfaction. The main criteria for customer satisfaction we know as speed, fit for use, and fair. Human always use analogical method for make some decisions, such as use historical experience for fit the similar problem. If the old case in after sales service could be saved dan organized efectivelly and sistematix, so we can use it to solve the new problem that have similar type. Method that use old case as a reference to solve new proble in Artificial Intelligent (AI) we always call Case Based Reasoning (CBR). This paper use CBR System for car sales after service problem. We also use Esteem software for improvement tools.After use this tools we get some resume that process in sevice become effective and efficient.